2003
DOI: 10.1289/ehp.5990
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorines, lead, and mercury in Akwesasne Mohawk youth.

Abstract: Most humans have detectable body burdens of polychlorinated biphenyls (PCBs), hexachlorobenzene (HCB), and p,p´-dichlorophenyldichloroethylene (p,p´-DDE), a metabolite of p,p´-dichlorodiphenyltrichloroethane (DDT). Native American communities may be at increased risk of exposure through subsistence-based diets and greater physical contact with contaminated soil and water. In this article we describe the levels of toxicants (PCBs, p,p´-DDE, HCB, mirex, lead, and mercury) among youth 10-17 years old (n = 271) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 47 publications
3
53
1
Order By: Relevance
“…Exposure assessment studies in the 1990s found some local animal species to have PCB, p,pЈ-DDE, HCB, and mirex levels above the US Food and Drug Administration human consumption tolerance limits. 20,21 Current levels of POPs in this study sample of 10-to 16.9-year-old participants largely reflect prenatal and lactational exposure 22 that is consistent with known levels of contaminants among adult women, attributable to past maternal consumption of locally caught, contaminated fish. 23 The history of local environmental pollution, the traditional reliance on locally caught fish and game, and the concerns of community members about the health effects of environmental pollutants prompted human health studies at Akwesasne, including an investigation of adolescent development.…”
Section: Settingsupporting
confidence: 53%
See 1 more Smart Citation
“…Exposure assessment studies in the 1990s found some local animal species to have PCB, p,pЈ-DDE, HCB, and mirex levels above the US Food and Drug Administration human consumption tolerance limits. 20,21 Current levels of POPs in this study sample of 10-to 16.9-year-old participants largely reflect prenatal and lactational exposure 22 that is consistent with known levels of contaminants among adult women, attributable to past maternal consumption of locally caught, contaminated fish. 23 The history of local environmental pollution, the traditional reliance on locally caught fish and game, and the concerns of community members about the health effects of environmental pollutants prompted human health studies at Akwesasne, including an investigation of adolescent development.…”
Section: Settingsupporting
confidence: 53%
“…22 Briefly, all data were collected by Akwesasne community members, without prior knowledge of participants' exposure status. All study protocols were approved by the institutional review board at the University at Albany, State University of New York, and informed consent was obtained from all participants.…”
Section: Participantsmentioning
confidence: 99%
“…Randomized cluster sampling techniques were utilized to collect samples and are described elsewhere (Santiago-Rivera et al, 2007;Schell et al, 2003). After informed consent was obtained, fasting blood samples (5 ml for serum cholesterol and triglycerides and 10 ml for organochlorines) were obtained from 335 adult Mohawks who lived on or near the Akwesasne Reservation in 1995-2000.…”
Section: Study Population and Blood Chemistry Analytic Proceduresmentioning
confidence: 99%
“…Data from the Santé Québec Health Survey (reported in Lévesque et al 1999;Schell et al 2003), cord blood studies conducted between 1993(Lévesque et al 2003Rhainds et al 1999) and data from the lead investigation done by Dewailly et al (2001) provide évidence of exposure to lead for the population of Nunavik. As outlined in Table 1, levels of lead concentrations in maternai blood from 1990-2000 were among the highest in circumpolar nations.…”
Section: Linking Lead Exposure and Traditional Foodsmentioning
confidence: 99%
“…Health elt'ccts of lead on women and children Ubiquitous to the natural environment, lead is a toxic métal with no proven biological function in living organisms (Sanborn et al 2002;Schell et al 2003;Scheuhammer et al 1998). According to Sanborn et al (2002Sanborn et al ( : 1287: "Studies indicate that, overall, there is no évidence for a threshold below which lead has been proven to hâve no adverse health effects.…”
Section: Gendered Dimensions Of Environmental Health 735mentioning
confidence: 99%